2005
DOI: 10.1002/joc.1222
|View full text |Cite
|
Sign up to set email alerts
|

ENSO-related rainfall anomalies in South America and associated circulation features during warm and cold Pacific decadal oscillation regimes

Abstract: El Niño/Southern Oscillation (ENSO)-related patterns of monthly reanalyzed upper-level circulation data and monthly rainfall time series over South America are revised for the 1948-1999 period considering the phases of the Pacific interDecadal Oscillation (PDO). The El Niño (EN) related composites show differences relative to the PDO phases as well as seasonal differences. EN signals in the South American rainfall are more conspicuous for the warm PDO (WPDO) regime, when seasonal differences are more pronounce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
133
0
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(159 citation statements)
references
References 35 publications
13
133
0
13
Order By: Relevance
“…These results are in agreement with previous composites of the summer precipitation anomalies for the ENSO extremes considering the PDO phases (Andreoli and Kayano, 2005;Kayano and Andreoli, 2007). Andreoli and Kayano (2005) explained most of the differences in the ENSO-related rainfall composites by the differences in the 200-hPa stream function composites between the PDO phases. Thus, the differences between the two periods reflect, in part, ENSO teleconnections over South America with the PDO background acting to enhance (weaken) the correlations when ENSO and PDO are in the same (opposite) phase.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in agreement with previous composites of the summer precipitation anomalies for the ENSO extremes considering the PDO phases (Andreoli and Kayano, 2005;Kayano and Andreoli, 2007). Andreoli and Kayano (2005) explained most of the differences in the ENSO-related rainfall composites by the differences in the 200-hPa stream function composites between the PDO phases. Thus, the differences between the two periods reflect, in part, ENSO teleconnections over South America with the PDO background acting to enhance (weaken) the correlations when ENSO and PDO are in the same (opposite) phase.…”
Section: Discussionsupporting
confidence: 92%
“…Andreoli and Kayano (2005) discussed the relationships of ENSOrelated rainfall and circulation anomalies over South America and the PDO. They found that El Niño signals in South American rainfall are more conspicuous for the warm PDO regime than for the cold PDO regime.…”
Section: Introductionmentioning
confidence: 99%
“…A comparação entre as duas regiões, geograficamente bastante próximas, não revelou concomitância nas tendências contínuas de elevação da Tmín. Em outro aspecto, o intervalo temporal de aproximadamente 12 anos entre a data de mudança de local do posto e a intersecção entre u(tn) e u*(tn), aliada às afirmações de MELLO et al (1994) relativas à série As influências dessa oscilação de escala multidecadal na variabilidade climática da América do Sul foram investigadas por ANDREOLI e KAYANO (2005) e KAYANO e ANDREOLI (2007). Nesses trabalhos, verifica-se que para a precipitação pluvial esse fenômeno age de maneira construtiva (destrutiva) quando o El Niño/Oscilação Sul (ENOS) e a ODP estão na mesma (oposta) fase.…”
Section: Resultsunclassified
“…As for the South American climate variability, only more recently has it been interpreted in the context of the PDO effects (ANDREOLI and KAYANO, 2005;KAYANO and ANDREOLI, 2007). These papers showed that the PDO creates a background for the ENSO teleconnections for the South American precipitation, acting constructively (destructively) when the ENSO and the PDO are in the same (opposite) phase.…”
Section: Introductionmentioning
confidence: 99%